1996
DOI: 10.2307/30141175
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and Cutaneous Carriage of Staphylococcus aureus in Hemodialysis Patients: The Effect of Nasal Mupirocin

Abstract: Fifteen of 20 hemodialysis patients who carried Staphylococcus aureus in their nares also carried the organism on their hands; 2 of 20 patients who did not carry S aureus in their nares carried S aureus on their hands (P < .001). Eighty-seven percent of patients who carried S aureus in their nares and on their hands carried the same strain at both sites. Intranasal mupirocin eliminated S aureus from both sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…Long-term nasal colonization with a persistent strain of S. aureus has been implicated as a source of organisms giving rise to bacteremia in hospitalized patients [19]. Persistent strains of S. aureus have also been found in patients receiving hemodialysis, continuous ambulatory peritoneal dialysis, and prolonged intravascular catheterization and in those with surgicalsite infections [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term nasal colonization with a persistent strain of S. aureus has been implicated as a source of organisms giving rise to bacteremia in hospitalized patients [19]. Persistent strains of S. aureus have also been found in patients receiving hemodialysis, continuous ambulatory peritoneal dialysis, and prolonged intravascular catheterization and in those with surgicalsite infections [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Three of 8 strains that caused recurrences would have been considered, on the basis of significant differences in antibiograms, to be the same as the isolate causing the initial infection (isolates 10-27, 11-30, and 11-32). PFGE showed that only 1 recurrence (caused by isolate 11-31) was a relapse (caused by isolate [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and this occurred after a 17-month interval ( figure 3).…”
Section: Patientsmentioning
confidence: 99%
“…Bei Nierenerkrankungen wurde generell eine erhöhte Suszeptibilität für schwere bakterielle Erkrankungen berichtet [6,9,11]. Abgesehen von den in der vorliegenden Arbeit untersuchten Aspekten ist anzunehmen, dass noch andere Faktoren die Komplikationsrate beeinflussen können.…”
Section: Tabelle 2 Risikofaktoren Für Einen Komplizierten Verlauf Einunclassified
“…As a result, efforts have been made to eliminate S. aureus colonization in an attempt to reduce the incidence of infection. Techniques include use of systemic antimicrobials, normal bacterial flora augmentation, antiseptic washes, and topical antimicrobials [10][11][12][13]. For a number of potential reasons, including efficacy and minimization of systemic antibiotic use, topical intranasal therapies have been recognized as a preferred method.…”
mentioning
confidence: 99%